Research of sources, factors and methods of efficiency of use of intellectual property objects - Maslak, M. V. (OKTAN PRINT, Czech Republic, 2023)
It has been proven that the most important types of effects from the use of intellectual products are economic (value indicators), scientific and technical (novelty, usefulness, reliability), market (demand, supply, price), social (social results) and environmental (indicators of the physical state of the environment). The integral economic effect from the implementation of intellectual and innovative projects is defined as the sum of all these types of effects. Thus, the integral economic effect of applying the results of scientific research and development includes all the components of reproductive development.
Дослідження джерел, факторів і методів ефективності використання об'єктів інтелектуальної власності
Keywords: intellectual property; effect; market; value indicators